Studies of Dioxouarnium(VI) Metal Complexes with a Schiff Base of 2-Aminopyridine - Arora, Kishore; Goyal, R.C.; Sharma, Susheel; Pathak, M.C. (Asian Journal of Chemistry, 2010)
A series of new dioxoranium(VI) complexes with a Schiff base derived from 2-aminopyridine, i.e., 2-N-[benzalidenel aminopyridine (BAPy) has been synthesized. Analytical, conductance, mol. wt. and spectral data reveal that the complexes have the general composition UO2X2(BAPy)2 (X = NO3, Br, I, NCS– or OAc–). Uranium atom is either 6 or 8 coordinated depending upon the anions present in these complexes. NMR and antifungal studies of representative compounds have been done successfully.